Circadian clock in plants: Linking timing to fitness. Issue 4 (5th March 2022) - Xu, Xiaodong; Yuan, Li; Yang, Xin; Zhang, Xiao; Wang, Lei; Xie, Qiguang
Abstract: Endogenous circadian clock integrates cyclic signals of environment and daily and seasonal behaviors of organisms to achieve spatiotemporal synchronization, which greatly improves genetic diversity and fitness of species. This review addresses recent studies on the plant circadian system in the field of chronobiology, covering topics on molecular mechanisms, internal and external Zeitgebers, and hierarchical regulation of physiological outputs. The architecture of the circadian clock involves the autoregulatory transcriptional feedback loops, post‐translational modifications of core oscillators, and epigenetic modifications of DNA and histones. Here, light, temperature, humidity, and internal elemental nutrients are summarized to illustrate the sensitivity of the circadian clock to timing cues. In addition, the circadian clock runs cell‐autonomously, driving independent circadian rhythms in various tissues. The core oscillators responds to each other with biochemical factors including calcium ions, mineral nutrients, photosynthetic products, and hormones. We describe clock components sequentially expressed during a 24‐h day that regulate rhythmic growth, aging, immune response, and resistance to biotic and abiotic stresses. Notably, more data have suggested the circadian clock links chrono‐culture to key agronomic traits in crops. Abstract : This review summarizes recent research on the circadian clock, an endogenous time‐keeping mechanism, covering how the circadian clock anticipates environmental and internal timing cues ( Zeitgebers ), the molecular architecture of core oscillators, the synchronization of cell‐autonomous clocks with circadian rhythm in whole plants, and circadian outputs including agronomic traits.